Czynniki jakości żywności - Strychalska-Rudzewicz, Anna (Factors of Food Quality, 2005)
The aim of this article is to present a problem of food products' quality in view of literature study. One tried to realize this aim, firstly describing idea of quality, next conditions which influence consumption behaviour and finally presenting evaluation of food quality in opinion of customers and producers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 310-315